2017
DOI: 10.20453/rmh.v28i3.3182
|View full text |Cite
|
Sign up to set email alerts
|

Monitoreo domiciliario de presión arterial y factores de riesgo cardiovascular en jóvenes estudiantes de medicina de una universidad privada en Lima, Perú

Abstract: Objetivo: Describir los niveles de presión arterial (PA) mediante el monitoreo domiciliario de la presión arterial (MDPA) y los factores de riesgo cardiovascular (FRC) en un grupo de jóvenes estudiantes de medicina de una universidad privada en Lima, Perú. Material y métodos: Estudio descriptivo de un grupo de estudiantes de medicina entre 18 y 23 años de edad, en quienes se midió la PA aplicando la técnica del MDPA. Los participantes llenaron un cuestionario para recolección de datos demográfico-epidemiológic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…When contemplating that a large majority of the subjects have a significant family history of diseases (present exclusively or in association), as well as the sedentariness categorized in more than half of the sam ple, and the important percentage of individuals who follow an atherogenic diet, a relationship between these factors with the alterations found in the sample's anthropometric values could be established. These results are comparable with other studies carried out in Spain 1 and in Peru 19 , in which it is also indicated that sedentary lifestyle affects women most of the time, with direct effects on their abdominal circumference and BMI. Nonetheless, men were not exempt from anthropometric abnormalities, given that 8% of the people in whom obesity was identified, a subtle majority was integrated by males, in whom alterations in abdominal circumference (47.8%) and in the WHR (19.4%) were also found, although in a smaller proportion.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…When contemplating that a large majority of the subjects have a significant family history of diseases (present exclusively or in association), as well as the sedentariness categorized in more than half of the sam ple, and the important percentage of individuals who follow an atherogenic diet, a relationship between these factors with the alterations found in the sample's anthropometric values could be established. These results are comparable with other studies carried out in Spain 1 and in Peru 19 , in which it is also indicated that sedentary lifestyle affects women most of the time, with direct effects on their abdominal circumference and BMI. Nonetheless, men were not exempt from anthropometric abnormalities, given that 8% of the people in whom obesity was identified, a subtle majority was integrated by males, in whom alterations in abdominal circumference (47.8%) and in the WHR (19.4%) were also found, although in a smaller proportion.…”
Section: Discussionsupporting
confidence: 91%
“…CVRFs correspond to those biological signs, acquired habits and characteristics of the individual that are most frequently associated with the statistical risk to predispose the development of a CVD in the coming years 18,19 . CVDs are preventable if measures on these factors are taken, some of which are fortunately modifiable 4,20 ; the World Health Organization (WHO) considers as CVRFs: systemic arterial hypertension, overweight, obesity, inadequate diet (atherogenic), dyslipidemia (hypercholesterolemia, hypertriglyceridemia, increased LDL cholesterol, and decreased HDL cholesterol), smoking, alcohol consumption, physical inactivity or sedentariness, male sex, age (men > 55 years, women > 65 years), family background and genetics, stress, diabetes mellitus, and the presence of another CVD 5,8,21 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies followed a cross-sectional, case-control and cohort design. Most of the articles were from Brazil (19) 30 35 , 37 45 , 48 – 51 while the others were from Chile (3) 29 , 36 , 46 and Peru (1) 47 . The instrument and methodology to measure NC was reported in 19 studies ( Table 2 ) 29 , 31 34 , 36 , 37 , 39 46 , 48 , 49 – 51 .…”
Section: Resultsmentioning
confidence: 99%
“…From all the captive population articles, 4 of these included university students 31 , 32 , 34 , 47 and also reported the mean NC ( Table 2 ). The minimum and maximum mean NC in this captive population were 33.66cm and 37.10cm, respectively; in men were 36.95cm and 37.30cm, respectively; and in women the minimum and maximum values were 32.02cm and 33.50cm, respectively ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation